Effect of Online Product Presentation on the Purchase Intention of Wearable Devices: The Role of Mental Imagery and Individualism–Collectivism - Wu, Jinnan; Wang, Fang; Liu, Lin; Shin, Donghee (Frontiers in Psychology, 2020)
The main objective of this study was to investigate how and when online product presentation influences individual purchase intention of wearable devices in China. This study hypothesized that online product presentation would influence individual mental imagery, which, in turn, would impact purchase intention through perceived social risk and positive emotion, but this effect would be moderated by individualism-collectivism value at the individual level. We performed a laboratory experiment (2×2) to collect the data (N=254). The experimental results indicated that there was a significant interaction effect between the product feature presentation video and usage scenario presentation picture on mental imagery. In addition to a direct effect, mental imagery had an indirect effect on purchase intention through perceived social risk and positive emotion. Additionally, the behavioral effect of perceived social risk was moderated by individualism-collectivism. Specifically, compared with individualists, perceived social risk had a stronger impact on collectivists’ purchase intention. This study contributes to a greater understanding of the mechanism through which online product presentation drives purchase intention, with a particular emphasis on how individualism-collectivism value at the individual level moderates consumers’ intention to purchase wearable devices.